Implementation of an Automatic Controlled Power Factor Correction System Utilizing Low-Cost Modules - Anees Abu Sneineh; Wael A. Salah; Alfian Ma'arif (Buletin Ilmiah Sarjana Teknik Elektro, 2026)
This paper presents the design and implementation of a PIC microcontroller-based power factor correction system using a stepped capacitor bank and low-cost analog measurement modules. The proposed design aimed to address the low power factor issue caused by inductive loads that intern increases the current, losses, and apparent power demand. The developed PIC-based controller integrated analog conditioning circuits for voltage, current, and phase-angle measurement. The proposed system acquires analog signals from a voltage transformer, a current transformer–op-amp module, and an AD8302-based phase detector, computes real, reactive, and apparent power in real time, and automatically connects or disconnects capacitor-bank steps to maintain the power factor within a predefined band (0.92–0.98). Experimental results on a 4 kW inductive load array indicated that the measurement error of the analog voltage module was approximately 1.32%, while the analog current module exhibited an error of around 3.02% in comparison to digital measuring instruments. Additionally, there was an improvement in the power factor from 0.865 to 0.935, with by a reduction in load current of approximately 7% and a decrease in load reactive power of about 35%. The proposed design confirms satisfactory operation for automatic capacitor-bank control in power factor correction applications.